Validity and Reliability of the Indonesian ADNM-8 in Nonclinical Adolescents - Irine Putri Shaliha; Melly Dina Aprillia; Ajeng Dwi Damayanti; Roselina Dwi Hormansyah (Universitas Andalas, 2025)
Adjustment Disorder (AjD) is a prevalent yet understudied mental health condition among adolescents, particularly in non-Western contexts. Despite its clinical relevance, validated instruments for assessing AjD in Indonesian youth are limited. This study aimed to evaluate the reliability and construct validity of the Indonesian version of the Adjustment Disorder New Module-8 (ADNM-8) as a screening tool for adolescents. Using stratified random sampling, 494 adolescents aged 11–18 years from urban areas in Java, Indonesia, were recruited. Participants were school-attending adolescents who had experienced at least one significant life stressor. The adaptation process included forward translation, expert-based content validation, and back translation to ensure linguistic and conceptual equivalence. Psychometric evaluation involved internal consistency analysis using Cronbach’s alpha and confirmatory factor analysis (CFA) with the DWLS estimator to accommodate ordinal data. The Indonesian ADNM-8 demonstrated strong internal consistency (α = 0.890). CFA results showed good incremental model fit (CFI = 0.965; TLI = 0.951), although RMSEA was elevated (0.143), indicating a limitation possibly related to model complexity. Overall, the findings support the Indonesian ADNM-8 as a reliable and valid screening instrument for AjD in adolescent populations.